ANALISIS PEMBERIAN HAK-HAK NORMATIF TERHADAP TENAGA KERJA ALIH DAYA SEBAGAI TENAGA KERJA PENUNJANG KEGIATAN OPERASIONAL OLEH PT. BANK SUMUT (STUDI DI PT. BANK SUMUT) - Rizki Alisyahbana; Suhaidi Suhaidi; Agusmidah Agusmidah; Mahmul Siregar (Universitas Sumatera Utara, 2018)
ABSTRACT In this study, the study was conducted at PT. The Bank of North Sumatra is linked with the planned appointment of thousands of TKAD’s to non permanent Non-Career Employees, resulting in 90 (Nineteen) TKAD’s not applying to new outsourcing companies considered to have resigned. As a result of the resignation, the TKAD is in accordance with the provisions in force at PT. Bank of North Sumatra and Cooperation Agreement on Manpower Services Delivery No. 01 / DKU-RT / SPj / 2014 dated January 28, 2014 between PT. Bank of North Sumatra with PT. Purna Karya Sejahtera was awarded